Well-Being and Satisfaction of Nurses in Slovenian Hospitals: A Cross-Sectional Study - Lorber, Mateja (Zdr Varst, 2020)
INTRODUCTION: Well-being is one of the most important factors in whether nurses decide to remain in the nursing profession. This study aims to examine well-being and satisfaction among nurses working in Slovenian hospitals and to identify the related demographic factors. METHODS: This descriptive cross-sectional study uses standardised instruments. The sample included 640 nurses working in Slovenian hospitals. The difference between individual variables were analysed using the Mann-Whitney and Kruskal-Wallis tests. RESULTS: Nurses self-assessed their satisfaction and well-being as moderate. Forty-seven per cent of nurses were satisfied with their job, 49% assessed their psychological well-being as good, 52% were often exposed to stress at the workplace and 30% were always exposed to stress at the workplace. Levels of job satisfaction (p=0.031), psychological well-being (p=0.029) and subjective well-being (p=0.014) were found to differ significantly according to level of education, while levels of job satisfaction (p=0.005), life satisfaction (p<0.001), psychological well-being (p<0.001) and subjective well-being (p<0.001) were also found to differ according to years of nursing service and from hospital to hospital (p<0.001). CONCLUSIONS: The key finding of the study is that nurses are moderately satisfied with their work and life and that they display moderate levels of psychological and subjective well-being. Hospitals can be successful and achieve the goals of the organisation if their employees are satisfied with work and enjoy good levels of well-being. Hospital management have to recognise the importance of ensuring that nurses and other employees are satisfied and healthy.